aΑ+bΒ>Product
1. d[A] 1. d[B]
v=———(———) = ———(———)=k[A][B]
-a. dt -b. dt
d[A]
—(———)=ak[Α][Β]
dt

n¡ = n0. + εν¡
[A] = [A0] -aε
[Β] = [Β0] -bε
[Α0]—[Α] [B0]—[B]
ε= —————— = ——————
a. b
[A0]—[A]
[B]=[B0]—b(——————)
a
b. b
=[B0]—(—)[A0]+(—)[A]
a a
b
=α. + —[A]
a
d[A] a
———=ak[A](α+—[A])
dt b

[Α] d[A] t
∫ ———————— = ∫ akdt
[Α0] b 0
[A]+(α+—[A])
a
1 x y
————————— = ——— + ————
b [A] b
[A]+(α+—[A]) (α+—[Α])
a a
b
x(α+—[A]) + y[A]
a
———————————
b
[A](α+—[A])
a
b
[A]°xα+(Χ— + y)[A]
a
———————————
b
[A](α+—[A])
a
xα=1
{ b
χ— + y =0
a
1. b -b
x=— y=-x—= ———
α a. aα b
———
[A] α. [A] αa. t
∫ ———d[A]—∫ ————— =- ∫ kadt
[A0] [Α] [A0] b 0
α+—[A]
a
b
[A] α+ —[A]
1 1 a a
—(—ln———) —(——(—)ln——————)=-kat
α [A0] αa. b b
α+—[A0]
a
1 [A] 1. [B]
—(—ln———) —(—ln———)=-kat
α. [A0] α [B0]

1. [A][B0]
—ln————— = kat
α. [A0][B]
1. [A][B0]
———————ln—————=kat
b [A0][B]
[B0]—(—[A0])
a
1. [A][B0]
———————ln———— = kt
b[A0]—a[B0] [A0][B]

共 0 則回應

馬上回應搶第 1 樓...
回應...